THE MAIN TOOL FOR TREATING DISEASES IS PHYSICAL EDUCATION (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
In the address of the president of the Republic of Uzbekistan Shavkat Mirziyoyev to the Supreme Assembly, we have put before us the exaltation of the foundation of the third renaissance in our country, for which we need to create environments and conditions that will educate the New Khwarazmians, Berunians, Ibn Sina, Ulugbek, Navoi and Babur. In this, first of all, the development of education and upbringing, the decision-making of a healthy lifestyle, the development of Science and innovation should serve as the main pillars of our national idea.It follows that physical culture is an area of social activity aimed at maintaining and strengthening human health in the process of conscious physical activity.Physical culture is part of culture, it is a set of values, criteria and knowledge created and used by society for the purpose of physical and intellectual development of human abilities, improvement of its physical activity and the formation of a healthy lifestyle, social adaptation through physical education, physical education and physical development. [1]The human body receives from the external environment all the substances necessary for full life. At the same time, a person receives not only useful substances, but also many irritating substances that contain moisture, sunlight and other harmful effects of production, which prevent him from living a healthy happy life. Therefore, in order for the human body to quickly adapt to any negative environmental factors and respond to environmental influences in a timely manner, it needs a lot of energy, strength in combination with the enhanced function of the immune system.Exercise should be considered not only as a means of rest, hobby and entertainment, but also as a means of ensuring the safety of Health. [2] thus, if exercise is added to a balanced diet, then you can improve the quality of your health, body and, most importantly, your inner state, mental health. It can serve to reveal in full blood that the main means of treating diseases is physical education.